Gender Issues in Children’s Literature: An Analysis of Fairytales - Tahira Akbar, Ra’ana Malik, Farooq-e-Azam (PJE, 2023)
This paper intends to explore the reasons of gender discrimination in different segments of Pakistani society at grass root level. This study is based on qualitative content analysis of children’s literature from which the most popular corpse of ten English fairytales purposively. Activities of different characters along with their social were selected and economic status, behavioral traits, gendered messages and thematic roles were analyzed by using coding frame for manifest and stimulus clues for latent information. This content analysis research indicates that gender difference is an integral part of the fairy tales which shows female gender inferior to male. A detailed qualitative analysis of these selected fairytales cited that gender issues start from titles and prevail throughout the fairytales. Males had proper names but girls were known with their attributive names in the titles. The study suggests a need for drastic change behaviorally, psychologically and materially (in our children’s literature and particularly in fairytales) to keep pace with the 21st century, which demands us to be more creative, active and innovative with scientific approach instead of becoming an escapist.